Biochemical and molecular impacts of glyphosate-based herbicide on the gills of common carp. (September 2019) - Ma, Junguo; Zhu, Jingyi; Wang, Wanying; Ruan, Panpan; Rajeshkumar, Sivakumar; Li, Xiaoyu
Abstract: Glyphosate (GLY)-based herbicide, one of the most widely used herbicides, might cause a series of environmental problems and pose a toxicological risk to aquatic organisms. However, data on the potential hazard and toxicity mechanism of GLY to fish gills are relatively scarce. In this study, a subacute toxicity test of common carp ( Cyprinus carpio L.) treated with commercial GLY at 52.08 and 104.15 mg L −1 for 7 d was conducted. The results revealed that GLY exposure significantly inhibited Na + /K + -ATPase and increased AST and ALT activities in the fish gills. The biochemical assays results revealed that GLY treatment remarkably altered the transcriptional levels of HSP70 and HSP90; inhibited the activities of SOD, CAT, GPx, GR, and T-AOC; reduced the contents of GSH, but remarkably promoted MDA and PC contents, suggesting that GLY exposure induced oxidative stress and lipids and proteins damage in the carp gills. Further research revealed that GLY exposure also promoted expression of NF-κB, iNOS, IL-1β, IL-6, IL-8, and TNF-α; altered the levels of IL-10 and TGF-β, indicating that GLY exposure induced inflammatory response in the fish gills. Additionally, we found that GLY exposure activated apaf-1 and bax and inhibited bcl-2, induced caspase-9 and caspase-3 expression and caused remarkable histological damage in the fish gills. These results may further enriches the toxicity mechanistic theory of GLY to fish gills, which may be useful for the risk assessment of GLY and aquatic organism protection. Graphical abstract: Image 1 Highlights: Glyphosate-exposure inhibited Na + /K + -ATPase activity of carp gills. Glyphosate caused oxidative stress and inflammatory response in fish gills. Glyphosate induced mitochondria-mediated apoptosis in carp gills. Glyphosate-exposure caused out of function and structural damage in fish gills. Abstract : GLY treatment induces oxidative stress and inflammatory response, and causes mitochondria-mediated apoptosis in the fish gills.